2011
DOI: 10.1016/j.ajpath.2010.12.025
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Ligand ITE Inhibits TGFβ1-Induced Human Myofibroblast Differentiation

Abstract: Fibrosis can occur in any human tissue when the normal wound healing response is amplified. Such amplification results in fibroblast proliferation, myofibroblast differentiation, and excessive extracellular matrix deposition. Occurrence of these sequelae in organs such as the eye or lung can result in severe consequences to health. Unfortunately, medical treatment of fibrosis is limited by a lack of safe and effective therapies. These therapies may be developed by identifying agents that inhibit critical steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 58 publications
3
55
0
1
Order By: Relevance
“…Soluble collagen was measured in cell supernatants as previously described (20). Briefly, 5 l of cell supernatants were applied to a PVDF membrane using a vacuum manifold (Schleicher and Schuell, Keene, NH) under nondenaturing conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Soluble collagen was measured in cell supernatants as previously described (20). Briefly, 5 l of cell supernatants were applied to a PVDF membrane using a vacuum manifold (Schleicher and Schuell, Keene, NH) under nondenaturing conditions.…”
Section: Methodsmentioning
confidence: 99%
“…ITE has also been shown to possess AHR-independent biologic activity, such as the inhibition of transforming growth factor-b1-mediated myofibroblast differentiation, which prevents fibrosis within human tissue (Lehmann et al, 2011). The AHR ligand ITE has many biologic activities, but its classification as an "endogenously" derived compound remains to be established.…”
Section: Host Metabolism Of Indolesmentioning
confidence: 99%
“…This finding is consistent with our report that the AHR ligand ITE blocked myofibroblast formation in mouse lung fibroblasts. 37 Another recent report reveals that the AHR ligand kynurenine prevents collagen production in dermal fibroblasts and possesses antifibrotic properties in a mouse model of skin scarring. 40 Myofibroblasts also express high levels of a-SMA, which localize to large stress fibers.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in some contrast to our earlier study in which it was observed that ITE's ability to block myofibroblast formation was largely AHR independent. 37 However, this study was performed in fibroblasts derived from either wild-type or AHR knockout mouse lung tissue. The different findings could be a result of either species-or tissue-specific differences in the AHR and TGF-b pathways.…”
Section: Discussionmentioning
confidence: 99%